An Experimental Study on Anchoring Effect of Consumers’ Price Judgment Based on Consumers’ Experiencing Scenes - Zong, Yi; Guo, Xiaojie (Frontiers in Psychology, 2022)
Consumers are prone to cognitive biases in decision-making due to the impact of time restrictions, specific environment and project inducements in the process of experience. Compared with traditional marketing scenarios, it is easy to bias decision makers due to the existence of anchor information. Research on anchoring effect focuses on psychology, economics, law, and medicine instead of consumers’ price judgment. This paper uses the experimental research to explore the existence and influencing factors of anchoring effect when consumers judge and estimate the price of a product in experiencing scenes. In this paper, the hypothesis is that anchoring effect exists and is influenced by factors including anchor value, gender, emotion, personality, knowledge and skill, time pressure, early warning indication, cognitive need and self-confidence level under external and internal anchor conditions. Subjects judged and estimated different prices after product experience through the design of different decision-making scenarios of external anchors (high anchors, low anchors) and internal anchors, and finally, the anchoring index (AI) and the mean skew index were used to calculate the anchoring effect. The experimental results showed that consumers were affected by anchoring effect when making price judgment in experiencing scenes. In addition to the factors of time pressure and the self-confidence level, gender, personality, knowledge and skill all had a significant influence on anchoring effect under external anchor conditions. Finally, this paper provides advice for enterprise marketing planners including setting reasonable anchor values, highlighting the design of experiencing scenes and developing differentiation strategies.